The effect of buoyancy force in computational fluid dynamics simulation of a two-dimensional continuous ohmic heating process - Elfakie, Elzubier Ahmed Salih; Choong, Thomas Shean Yaw; Spotar, Sergei Y.; Chin, Nyuk Ling; Mohammed, Ibrahim Omer (Science Publications, 2009)
Problem statement: Earlier work on ohmic heating technique focused on viscous food and foods containing solid particles. In this study, the use of ohmic heating on sterilization of guava juice is carried out. Computational fluid dynamics is used to model and simulate the system. Approach: Investigate the buoyancy effect on the CFD simulation of continuous ohmic heating systems of fluid foods. A two-dimensional model describing the flow, temperature and electric field distribution of non-Newtonian power law guava juice fluid in a cylindrical continuous ohmic heating cell was developed. The electrical conductivity, thermo physical and rheological properties of the fluid was temperature dependent. The numerical simulation was carried out using FLUENT 6.1 software package. A user defined functions available in FLUENT 6.1 was employed for the electric field equation. The heating cell used consisted of a cylindrical tube of diameter 0.05 m, height 0.50 m and having three collinear electrodes of 0.02 m width separated by a distance of 0.22 m. The sample was subjected to zero voltage at the top and bottom of electrodes while electrical potential of 90 volts (AC 50-60 Hz) was set at the middle electrode. The inlet velocity is 0.003 m sec1 and the temperature is in the range of 30-90°C. Results: The simulation was carried with and without buoyancy driven force effect. The ohmic heating was successfully simulated using CFD and the results shows that the buoyancy has a strong effect in temperature profiles and flow pattern of the collinear electrodes configuration ohmic heating. A more uniform velocity and temperature profiles were obtained with the buoyancy effect included. Conclusion: For accurate results, the inclusion of buoyancy effect into the CFD simulation is important.